2018
DOI: 10.21037/jtd.2017.10.16
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for malignant pleural mesothelioma: an international guidelines review

Abstract: Currently there is no universally accepted surgical therapy for malignant pleural mesothelioma (MPM). The goal of surgery in this dismal disease is a macroscopic complete resection (MCR) and there are two types of intervention with a curative intent. At one side, there is the extrapleural pneumonectomy (EPP) which consists in an en-bloc resection of the lung, pleura, pericardium and diaphragm and at the other side, there is pleurectomy/decortication (P/D) a lung-sparing surgery. Initially, EPP was considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
(40 reference statements)
0
37
0
Order By: Relevance
“…Patients face a devastating prognosis of 12 months median survival only after diagnosis [1]. Despite recent-and, in part, promising-developments regarding both systemic therapy and cytoreductive surgery, MPM remains a clinical challenge, especially when it comes to treatment allocation [2,3]. Furthermore, the optimal (multimodal) treatment regimens still remain to be defined from the available arsenal of immune therapy, surgery, radiation and systemic treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients face a devastating prognosis of 12 months median survival only after diagnosis [1]. Despite recent-and, in part, promising-developments regarding both systemic therapy and cytoreductive surgery, MPM remains a clinical challenge, especially when it comes to treatment allocation [2,3]. Furthermore, the optimal (multimodal) treatment regimens still remain to be defined from the available arsenal of immune therapy, surgery, radiation and systemic treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative debulking surgery and parietal pleurectomy are performed to provide symptom control in MPM. This type of surgery is not undertaken with a curative intent but removal of the visceral pleura, and relieve of a trapped lung can, reduce chest wall pain 50. Video-Assisted Thoracic Surgery (VATS) offers a minimally invasive alternative for patients who are unfit for radical EPP or extended P/D.…”
Section: Surgerymentioning
confidence: 99%
“…Epidemiological studies have proven that occupational or environmental exposure to asbestos is involved in the development of MPM and the incidence of MPM is predicted to continue increasing. Multimodal therapy including surgical treatments such as extrapleural pneumonectomy and pleurectomy/decortication is applicable only to patients with early‐stage disease and good performance status 1 . Systemic chemotherapy with cisplatin and pemetrexed is the only approved regimen with the evidence to prolong overall survival of inoperable patients, but the median overall survival time of patients who are treated with this regimen is 12 mo after diagnosis 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal therapy including surgical treatments such as extrapleural pneumonectomy and pleurectomy/decortication is applicable only to patients with early-stage disease and good performance status. 1 Systemic chemotherapy with cisplatin and pemetrexed is the only approved regimen with the evidence to prolong overall survival of inoperable patients, but the median overall survival time of patients who are treated with this regimen is 12 mo after diagnosis. 2,3 Although recent clinical phase II studies demonstrated that nivolumab, an anti-programmed death-1 (PD-1) antibody, showed promising clinical activity in patients with relapsed MPM, there has been a lack of definitive evidence to support the practical use of nivolumab to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%